Solve for \( b \). \begin{tabular}{l}\( b=(b-a) m \) \\ \( \frac{\square}{\square} \) \\ \hline\end{tabular}
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
Let's first rewrite the equation for clarity: \[ b = (b - a) m \] To solve for \( b \), we can start by distributing \( m \): \[ b = bm - am \] Now, let's isolate all the terms involving \( b \) on one side. We'll add \( am \) to both sides: \[ b + am = bm \] Next, we can rearrange the equation to factor out \( b \): \[ b - bm = -am \] Factoring out \( b \) gives us: \[ b(1 - m) = -am \] Now, to find \( b \), we'll divide both sides by \( (1 - m) \) (assuming \( m \neq 1 \)): \[ b = \frac{-am}{1 - m} \] And there you have it; solving for \( b \) yields: \[ b = \frac{-am}{1 - m} \] Just remember to be cautious when \( m = 1 \), as that would make the denominator zero!